Pelatihan Metode Bernyanyi untuk Pembelajaran Akidah Akhlak di TPA - Mukminin, Amir; Dedi Rismanto; Yekti Prihatin (Transformatif : Jurnal Pengabdian Masyarakat, 2022)
In Malangsari there is a non-formal learning institution about religion, namely the Al-Qur'an Education Park (TPA) Albarokah which is located at the Albarokah Mosque. TPA Albarokah teaches Iqra and Qur'anic Literacy, Fiqh, and Akidah Akhlak. The devotee conducts service by means of a Focus Group Discussion (FGD) with the ustaz. This devotion aims to teach the ustaz a method of singing about the adab of eating and drinking and knowing the ten angels of God and their duties. The function of this method is to make it easier for students to understand landfill material. Devotion is done by lectures and practices. As a result, students are easier to understand and memorize with the singing method.